The nation and the child : nation building in Hebrew children's literature, 1930-1970 - Dar, Yaʻel (Children's literature, culture, and cognition, 2018)
"The Nation and the Child - Nation Building in Hebrew Children's Literature, 1930-1970 is the first comprehensive study to investigate the active role of children's literature in the intensive cultural project of building a Hebrew nation. Which social actors and institutions participated in creating a Hebrew children's literature? How did they envision their young readership and what new cultural roles did they prescribe for them through literary texts? How tolerant was the children's literary field to alternative or even subversive national options? How did the perceptions of the "national child" change in the transition from the pre-state Yishuv to a sovereign state? This book seeks to provide answers to such questions by focusing on the literary activities of leading taste-setters and writers for children, from the most intense period of Israeli nation building - the 1930s and 1940s, the two last decades of the pre-state era, and the 1950s, the first decade following the establishment of the State of Israel in 1948 - through the 1960s, when the nation-building fervor gradually waned"--